Our South : geographic fantasy and the rise of national literature - Greeson, Jennifer Rae (Harvard University Press, 2010)
This work tracks the nation/South juxtaposition in US literature from the founding to the turn of the 20th century, through genres including travel writing, gothic and romance novels, geography textbooks, transcendentalist prose, and abolitionist address.